Anthropomorphic figurines and miniature beads from the Early Neolithic settlement of Ilindentsi, southwest Bulgaria - Małgorzata Grębska-Kulow; Maria Gurova; Petar Zidarov (Българско е-Списание за Археология, 2021)
The paper presents two types of small artefacts: anthropomorphic figurines and miniature beads, all of which were acquired during the excavations of the Early Neolithic settlement at Ilindentsi during 2011–2018. The anthropomorphic clay figurines are arranged in three groups: Group 1 – figurines with enlarged hips and buttocks (steatopygia); Group 2 – prism/parallelepiped shaped figurines and Group 3 – figurines with plastic projections on the head (buns or horns). One partially preserved marble figurine was also found. All of these objects show an interesting spatial distribution while being concentrated in two distant houses. All figurines confirm a general trend in the development of these objects in the central Balkans and northern Greece but also emphasise the supraregional contacts with the Pannonian Plain. Miniature beads are very characterisic of the Early Neolithic settlement at Ilindentsi. Forty-one beads have been found, most of them within the boundaries of house № 2. Thirty-six beads were made of clay and only five beads from other raw materials: shell, rock and mother-of-pearl. The collection of miniature clay beads from Ilindnetsi is unique, with no parallels from other contemporary sites in the Balkans. In terms of importance it places Ilindentsi right after emblematic Anatolian sites such as Çatalhöyük and Çukuriçi. The clay beads from Ilindentsi pose a number of questions about their place and role in the so-called Neolithic package; their function, social dimension and last but not least their expression of people’s specialized skills.